MODEL JIGSAW BERBANTU KARTU SOAL MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI - Siti Aisyah (Universitas Ngudi Waluyo, 2021)
The purpose of this classroom action research was to determine the increase in activity and learning outcomes of Mathematics learning in grade VI SD 2 Kesambi, Kudus Regency through the Jigsaw model assisted by question cards. The Jigsaw learning model is a variation of the Cooperative Learning model, which is a group learning process where each member contributes information, experiences, ideas, attitudes, to jointly improve the understanding of all members. The research was carried out in 2 cycles, each cycle of four stages, namely planning, implementing, observing and reflecting. It is proven by the existence of a jigsaw model assisted by a question card to improve learning outcomes from the initial conditions, cycle I, and cycle II. Classical completeness in the initial conditions was 17 students (49%), cycle I was 25 students (71%), in cycle II it was 29 students (83%). Likewise, student learning activities in the first cycle with a class average of 73 and in the second cycle it became 79